REVIEW OF BEARING CAPACITY OF FINNED CONCRETE SLABS BASED ON THE NUMERICAL VARIATION OF LENGTH - Amal, Tansa Ihwanul; Bachtiar, Vivi; Yusuf, Muhammad (Fakultas Teknik Universitas Tanjungpura, 2023)
In general, Pontianak and the surrounding area have soft soil characteristics with a low carrying capacity compared to other soil types. This condition is the leading cause of several construction failures, especially in constructing transportation or road facilities and infrastructure. One form of construction failure is the state of the road, which has experienced cracks and bumps in a relatively short time after the construction of the road. Innovations in road pavement construction are needed to overcome these conditions. This research aims to obtain the carrying capacity of reinforced concrete road pavement construction with fins by being given a layer of sand on cohesive and non-cohesive soils. This research was carried out by testing numerically through plate modelling with the PLAXIS 3D application and unique software in reviewing the modelling structure. In this study, the effect of fin length at a slope of 30 ° on increasing the ultimate load of slabs on cohesive and non-cohesive soils was investigated using the Elastic-Plastic method and with a computer program, which was then plotted into a graph of the relationship between load versus settlement and a diagram of the relationship between ultimate load vs. fin length. Based on the computer program output results, the five models' most significant soil maximum load (Pu) is 22.5 kN in the 40 cm fin length modelling. Even though they have different parameters, the two soils show the same results and behaviour. These results show that the most optimal modelling in this study is on a 40 cm long finned concrete slab because the soil carrying capacity is higher than other models.